Brain Atrophy and Hypomyelination Associated with Iatrogenic Cushing’s Syndrome in an Infant - Dogan, Sumeyra; Dogan, Mehmet S.; Tutunculer, Filiz; Yapici Ugurlar, Ozge; Genchellac, Hakan (Iranian Journal of Child Neurology, 2018)
<span style="line-height: 115%; font-family: 'Arial','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: TR; mso-bidi-language: AR-SA;" lang="EN-US">Prolonged use of topical corticosteroids, particularly in infants, albeit rare, may lead to Cushing's syndrome. Central nervous system abnormalities including brain atrophy and delayed myelination on cranial magnetic resonance imaging has been reported in patients with corticosteroid treatment. We herein report a 5-month-old female infant with brain atrophy and myelination delay that might be due to iatrogenic Cushing's syndrome caused by topical corticosteroid use.